CONTEMPORARY STAGE OF PEDAGOGICAL SCIENCE DEVELOPMENT IN CONTEXT OF GLOBALIZATION TENDENCIES - Oxana P. Chigisheva (Advanced Engineering Research, 2011)
Processes occurring on the theoretical and methodological levels of pedagogy in the modern period are considered. The emphasis is laid on the examination of the pedagogical projection of the globalization phenomenon, revelation of the dynamics and trends of pedagogical knowledge development as a theoretic construct aimed at the conceptualization of the world educational processes. The author’s view on the highly discursive issue of finding the research approach adequate to the contemporary conditions is represented.